2017
DOI: 10.1016/j.compositesb.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of dynamic failure progress and properties of 2D C/SiC composite from 173 K to 1273 K by SHTB

Abstract: Our work studies the dynamic properties of coated and uncoated 2D C/SiC composite material from 173K to 1273K by means of Split Hopkinson Tensile Bar. Examination of the failure process of the specimen by SIM D8 ultra high-speed camera and damage analysis help define the three phases of crack propagation, namely: the elastic pre-damaged phase, the yielding phase or the crack-initiating phase, and the failure phase or the phase of fast-spreading cracks. Experimental results also reveal that the dynamic tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…These proteins can function as scaffolds to assemble a superfamily of ubiquitin ligases known as cullin-RING E3 ubiquitin ligase (CRL) complexes, which is the largest E3 ligase family, with more than 300 members (Chen et al, 2015;Sarikas et al, 2011). During the past several years, emerging evidence has reported that the dysregulation of these cullins, in particular CUL4A and CUL4B, is associated with the occurrence of many cancers, such as breast cancer (Chen et al, 1998), colon cancer (Sui et al, 2017), hepatocellular carcinoma (Yuan et al, 2015), and osteosarcoma (Chen et al, 2017). At present, little is known regarding the mechanisms of CUL4A/4B overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins can function as scaffolds to assemble a superfamily of ubiquitin ligases known as cullin-RING E3 ubiquitin ligase (CRL) complexes, which is the largest E3 ligase family, with more than 300 members (Chen et al, 2015;Sarikas et al, 2011). During the past several years, emerging evidence has reported that the dysregulation of these cullins, in particular CUL4A and CUL4B, is associated with the occurrence of many cancers, such as breast cancer (Chen et al, 1998), colon cancer (Sui et al, 2017), hepatocellular carcinoma (Yuan et al, 2015), and osteosarcoma (Chen et al, 2017). At present, little is known regarding the mechanisms of CUL4A/4B overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…It is stated that EM shielding effect changes depending on the factors such as the ratio of the conductive fibers to the surfaces, the fabric structure, the number of layers as well as the frequency and layout angles of the fabric . In the literature, various studies have been carried out with raw materials such as boron, metal, carbon fibers, glass fibers, copper and polypropylene (PP) for EM shielding purposes for adults, children and particularly for infants (0‐2 years). Demirkurt et al prepared a fabric‐based composite using boron carbide and epoxy (Tubicoat CRO), and it was observed that boron carbide‐doped composite fabrics gave reliable results for EM shielding above 10 dB at frequencies between 1.9 and 2.9 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the EM shielding effect is up to 124 dB in the frequency range from 300 kHz to 1.5 GHz. Cheng et al studied the EM shielding effect of knitted fabrics made of PP reinforced copper/glass fibers. In the study, PP was used in matrix phase and glass fiber reinforcement material.…”
Section: Introductionmentioning
confidence: 99%
“…7 PLA is one of the most well-known types of biodegradable polymer for replacement of commodity petroleum-based plastics. 8 It is a type of linear aliphatic polyester derived from biomass, which is biodegradable and has potential to be applied in variety of large-scale industrial applications such as packaging and biomedical application areas. [9][10][11] It provides mechanical, good optical, physical and barrier properties compared to the existing petroleum-based polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all that, the major weakness of PLA that hinders its application could be its low T g of approximately 60 ∘ C and brittleness that causes low deformation at break. 11,12 Thus, much research has been done to overcome these shortcomings by incorporating other types of polymers, 9,[12][13][14][15] fillers, 8,11,[16][17][18] natural rubber, [19][20][21][22][23][24] etc.…”
Section: Introductionmentioning
confidence: 99%